Femoroacetabular impingement in ice hockey athletes - Silvestri, M. A.; Cleather, D. J.; Patterson, S.; Legg, H. S. (The Journal of Strength and Conditioning Research, 2023)
Femoroacetabular impingement (FAI) in ice hockey is a concern for many athletes. The biomechanics of skating and the injury mechanism, prevalence, identification, and treatment protocols currently available for FAI in ice hockey athletes are important for all coaches and practitioners to understand. This article discusses the underlying anatomical issues and biomechanical considerations surrounding FAI. Furthermore, this article describes the interventions that can be used when encountering FAI and well-established protocols to aid in the return to play. Finally, prevention strategies that can aid in injury prevention are discussed.